NEEDS ANALYSIS FOR THE EVALUATION OF TEACHER TRAINING PROGRAMS WITHIN THE MINISTRY OF RELIGIOUS AFFAIRS IN MALUKU AND NORTH MALUKU PROVINCES - Arsyil Waritsman; Theresia Laurens; Izaak Hendrik Wenno (RADJA PUBLIKA, 2026)
This study aims to (1) Identify the evaluation needs of teacher training programs within the Ministry of Religious Affairs of Maluku and North Maluku Provinces; (2) Analyze the factors that influence evaluation needs in the context of the island provinces; and (3) Describe the evaluation practices that have been implemented and examine the extent to which these practices meet the identified evaluation needs. The method used in this study is qualitative. The subjects in this study were two teachers. The data collection techniques used were non-test methods, including interviews and document analysis. Data analysis was carried out through three stages, namely: (1) Data Reduction, (2) Data Display, and (3) Conclusion Drawing and data verification. The results of the study indicate that (1) Teachers within the Ministry of Religious Affairs require systematic, continuous and comprehensive evaluation of training programs; (2) The need for teacher training evaluation is significantly influenced by the context of the island region such as geographical factors, limited electricity and internet infrastructure, and sea transportation constraints that affect the implementation and evaluation models that can be applied and (3) Current teacher training evaluation practices are still oriented towards process evaluation and participant satisfaction. The research findings are expected to provide contextual recommendations for developing teacher-training evaluation models that are relevant to the characteristics of the Maluku and North Maluku regions, as well as further strengthening the evaluation system within the Ministry of Religion.